Feasibility of bulk shipping investments - investment into the handysize segment with time horizon between 2023 and 2027 - Ang, Chia Chee (Nanyang Technological University, 2022)
The paper is based on the forecasted freight rate provided in Volume 1, which was determined by evaluating the market outlook. It will continue to study the feasibility in investing into the Handysize bulk market from 2023 to 2027. The paper starts by analyzing the different types of charters for various acquisition and employment combinations. Followed by the factors affecting the revenues and cost of the Handysize segment. Then, the paper will analyse the historical data and market trend of the time charter rate and cost component. Next, forecast time charter hire rate and daily operating cost for cashflow analysis, where source of value will be influenced. As initial capital outlay is not considered in cashflow analysis, hence the paper will work on the residual value of the vessel to obtain Return on Asset (ROA). The results obtained from cashflow and ROA analysis show contradiction, but employment strategies are akin. Deploying a vessel on TCT for 5 years seems to be the most feasible option in all types of acquisition. Although the analysis of Return on Asset of the Handysize segment provides investors with a glimpse of the outcome of various permutations, whether the Handysize bulk carrier market is a market worth investing in to deploy their assets and capitalize on fleets will be discussed in Volume 3.